Lessons learned from black soldier fly farming for circular livelihoods in Kenya - Adamtey, Noah; Kibet, J.; Mwangi, E.; Somorin, Tosin; Gebrezgabher, Solomie A. (International Water Management Institute, 2025)
The September 2025 assessment in Kisumu County, Kenya, examined operational challenges affecting IWMI’s Black Soldier Fly (BSF) Production Facility and private BSF farms, with the goal of identifying improvements in efficiency, waste sourcing, and productivity.